Preface (Preface_V_XV) - Pearson, Birger A. (BrillOnline Reference Works, 2012)
This volume is the product of many years of work; yet it is with some trepidation that I submit it herewith to the public. The fragmentary status of the two codices published here has made the work much more difficult and time-consuming than would have been the case had the material been preserved more completely